2017
DOI: 10.1016/j.athoracsur.2016.08.079
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Intraoperative Molecular Imaging Can Locate Metastases to the Lung

Abstract: Systemic ICG identifies subcentimeter tumor metastases to the lung in murine models, and this work provides proof of principle in humans. Future research is focused on improving depth of penetration into the lung parenchyma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 61 publications
(91 citation statements)
references
References 32 publications
3
88
0
Order By: Relevance
“…First, delivery of this dosage of ICG was well tolerated, which is consistent with our previous experiences with ICG (3). Second, we found that the addition of intraoperative imaging was efficient and addended only several minutes to the case duration.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…First, delivery of this dosage of ICG was well tolerated, which is consistent with our previous experiences with ICG (3). Second, we found that the addition of intraoperative imaging was efficient and addended only several minutes to the case duration.…”
Section: Discussionsupporting
confidence: 88%
“…Our group has previously reported successful utilization of near-infrared (NIR) fluorescent, real-time intraoperative imaging to improve pulmonary metastasectomy (3). In this report, we detail successful utilization of this approach to enhance accurate identification of malignancy during resection of a thymic carcinosarcoma in a patient that previously underwent neoadjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these advantages, 5-ALA is not FDA-approved. Indocyanine green, however, is a readily available, FDA-approved NIR fluorescent drug which has promise as a tumor optical contrast agent [1116]. Although the Second Window ICG technique has been studied in a rodent model of lung cancer, we hypothesized that Second Window ICG could also provide optical contrast of brain tumors.…”
Section: Discussionmentioning
confidence: 99%
“…By exploiting this delivery method, NIR cameras can be used in the operating room environment to visualize ICG accumulation within tumors. Our lab has used this technique in a variety of tumor types, including lung, ovarian, colorectal, breast, and metastases [9, 1117]. …”
Section: Introductionmentioning
confidence: 99%
“…Several groups have demonstrated the efficacy of IMI for the detection of intrathoracic and extrathoracic malignancies (7,(12)(13)(14)(15)(16)(17)(18)(19). Our group has investigated two different tracers for the intraoperative detection of pulmonary nodules and occult metastases-indocyanine green (ICG) and a folate receptor alpha (FRα) targeted fluorophore.…”
Section: Preclinical Studiesmentioning
confidence: 99%